(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Chuvasova N. O. Psychological and pedagogical aspects of students professional creativity development. In the article a theoretical survey and analysis of scientific literature about professional creativity developing in up-to-date psychology, psychological and pedagogical fundamentals of students’ thinking are discussed and characterized in the article.